An Adaptive Gaze Tracking System in the Diverse Environment - Kao, Chiao-Wen; Chen, Hui-Hui; Wu, Shyi-Huey; Hwang, Bor-Jiunn; Lai, Hung-Sheng (International Journal of Informatics and Information Systems, 2022)
For understanding the learning effect, the gaze tracking is a more objective method to collect the data on eye movement and used to analyze the learning behaviors. In order to provide an analysis tool to apply in diverse environments, an adaptive gaze tracking system is proposed in this paper. This system can offer helpful suggestions for educators when improving the instruction. Additionally, the experimental results show that the estimation of gaze points was successful even when the distance and head rotation alter.